Constitutional Court Decision to Protect the Rights of Women and Children in Improving Justice and Legal Certainty - Riris Ardhanariswari; Muhammad Fauzan; Fathimah Azzahro (Faculty of Law, Universitas Pekalongan, 2023)
This paper aims to analyze how the Constitutional Court protects human rights, especially the rights of women and children. Through one of the powers of the Constitutional Court is to conduct a judicial review of the Constitution. The authority of the Constitutional Court is a push for the realization of the constitutionality of the law in order to protect human rights for everyone, including women and child right. The purpose is to analyze the extent to which the Constitutional Court performs its function as the guardian of the Constitution. The research uses statute approach, the comparative approach, the conceptual approach, and the historical approach, based on four judicial review cases: Constitutional Court Decision No.20/PUU-XI/2013 concerning Judicial Review No. 10 of 2008 of General Elections, Constitutional Court Decision No.46/PUU-VIII/2010 concerning Judicial Review Number 1 of 1974 on Marriage, Constitutional Court Decision No.22/PUU-XV/2017 concerning Judicial Review Number 1 of 1974 on Marriage, and Constitutional Court Decision No.24/PUU-XX/2022 concerning Judicial Review Number 1 of 1974 on Marriage. The results of the review demonstrate that: (1) there is an imbalance in legal products that harm women and children; and (2) the Constitutional Court has a mechanism to correct inequality in legal products through a judicial review mechanism. This paper finds that the Constitutional Court plays a significant role in safeguarding women's rights in law through judicial mechanisms. Moreover, this article provides an academic-based assessment of the Constitutional Court's decisions to provide optimal protection for the fulfilment of the rights of women and children.Keywords: Protection, Woman and Children, Rights, Constitutional Court